Influence of oncolytic strains of a new unclassified group of human rotaviruses on peripheral blood lymphocytes - O. I. Kit; S. Yu. Filippova; S. V. Timofeeva; A. O. Sitkovskaya; E. Yu. Zlatnik; S. A. Kolpakov; E. P. Kolpakova; E. S. Bondarenko; I. A. Novikova (Южно-Российский онкологический журнал, 2021)
Purpose of the study. Evaluation of the cytotoxic effect of strains RVK100 and RVK228 of a new unclassified group of human rotaviruses on human peripheral blood mononuclear cells in vitro.Materials and methods. As a material for the study, we used peripheral blood mononuclear cells of a healthy donor. The cells were exposed to two strains of rotaviruses RVK100 and RVK228 for 24 and 48 hours. The cytotoxicity of the tested viruses was assessed using the Colorimetric Cell Viability Kit I (WST-8) (PromoCell, Germany). Analysis of lymphocytes subpopulation composition was assessed on a FACSCantoII flow cytometer (BD, USA) using monoclonal antibodies to human antigens: CD3, CD4, CD8, CD16/56, CD19, CD45, CD38, HLA-DR.Results. According to the cell viability test, there was no significant decrease in the number of living cells in the samples with the addition of viruses in comparison with the control. On the contrary, after 48 hours of cultivation in the samples with the addition of RVK228, the number of living cells was significantly higher than in the control. The study of lymphocytes subpopulation composition showed a relative increase in the number of early activation markers on T cells in samples with viruses, which was also more pronounced in samples with the addition of RVK228.Conclusion. The investigated strains of rotaviruses have no cytotoxic effect on human peripheral blood mononuclear cells. Moreover, the RVK228 strain is likely to have the ability to activate lymphocytes.